The use of models in optimizing the field crop production in agricultural enterprise - MBA thesis - Munćan, Mihajlo (Applied Studies in Agribusiness and Commerce, 2010)
The full use of resource capacities of agricultural enterprises favorably affects the general increase in economic efficiency and rational production making them more competitive in the market. This creates the need for constant improvement of business strategies that uses all available resources to create the most profitable production. The main objective of this study was to find the ideal structure of production in agricultural enterprise and to enable the realization of maximum profit using the available production resources (land, mechanization, labor forces). As the basic method of planning, this study used the simplex method of linear programming which gives the most profitable sowing structure after detailed analysis of resources and achieved results, based on the limitations and gross margin. This work showed that the use of modern methods in production planning is one of the cheapest and safest methods for development of agricultural enterprises.